The Influence of Corporate Social Responsibility and Customer Retention on Customer Relationship Management Performance with the Mediating Effect of Customer Trust in SMEs of Ningxia Province, China - JIE, YANG; MAKMOR, NURKHALIDA BINTI; REHMAN, ASAD UR (Journal of Ecohumanism, 2024)
In recent years, e-commerce has experienced rapid expansion and developed as the mainstream business practice in small and medium-sized enterprises (SMEs) in developing areas of China. There are a variety of channels for consumers to purchase from. Therefore, maintaining customers is increasingly important. In the meantime, companies expect to gain more significant insights into their consumers’ demands to earn customer trust, thus achieving customer relationship management (CRM) performance. This study develops based on trust theory and consists of four latent variables: corporate social responsibility (CSR), customer retention, customer trust, and customer relationship management performance. The current study used probability and random sampling techniques. It conducted the questionnaire survey to collect data form managers of SMEs in Ningxia province of China. The Partial least square structural equation modeling (PLS-SEM) technique was used for this study. As a result, a total of 150 respondents were usable for these questionnaires. The study revealed that corporate social responsibility and customer retention have a positive effect on customer relationship management performance. Moreover, customer trust has been examined that it had a positive effect on customer relationship management performance. In addition, customer trust was discovered as a partial mediation between the relationship of corporate social responsibility, customer retention, and customer relationship management performance. Furthermore, based on the samples analyzed, the proposed model seems to be fitted considerably well. Therefore, this study intends to contribute to a better understanding of factors influencing customer relationship management performance in Chinese SMEs, thereby providing companies with practical ideas to improve overall performance.